ESTIMATOR NADARAYA-WATSON DENGAN FUNGSI KERNEL NORMAL DAN FUNGSI KERNEL KUADRATIK - Saskia Amalia Putri; Ayudita Rahmi Aristya; Nur Azizah Janad; Yudy Novindri Tadale; Lilies Handayani (Journal of System and Computer Engineering (JSCE), 2022)
The Human Development Index (HDI) is a comparative measurement of life expectancy, literacy, education and living standards for all countries around the world. The human development index is used to classify whether a country is a developed country, a developing country or a backward country and also to measure the effect of economic policies on the quality of life. The purpose of this study is to find out how the percentage of poor people and the unemployment rate are related to the human development index in Central Sulawesi. In this study, the Nadaraya-Watson kernel regression method was used with a regression comparison between normal kernel functions and quadratic kernel functions. Based on the results of the study, the best model on X1 (percentage of poor people) with the smallest MSE value is the CV.LS method with a bandwidth value of 1.369349, and for the best model on X2 (open unemployment rate) with the smallest MSE value, namely the CV.AIC method. with a bandwidth value of 1.331878.